The pattern of tumor progression on first-line immune checkpoint inhibitor-based systemic therapy for Chinese advanced hepatocellular carcinoma –CLEAP 004 study - Yang, Chao-Xu; Pan, Yang-Xun; Ye, Feng; Zhu, Xiao-Dong; Xue, Jun; Li, Xi; Yuan, Zhen-Gang; Zhang, Lan; Xu, Li; Chen, Yong-Jun; Wang, Nan-Ya; Sun, Hui-Chuan; et al. (Frontiers in Immunology, 2024)
For decades, stratification criteria for first-line clinical studies have been highly uniform(1). However, there is no principle or consensus for restratification after systemic treatment progression based on immune checkpoint inhibitors (ICIs). The aim of this study was to assess the patterns of disease progression in patients with advanced hepatocellular carcinoma (HCC) who are not eligible for surgical intervention, following the use of immune checkpoint inhibitors. This is a retrospective study that involved patients with inoperable China liver stage (CNLC) IIIa and/or IIIb. In this investigation of advanced hepatocellular carcinoma among Chinese patients treated with immune checkpoint inhibitors, we identified four distinct progression patterns (p-IIb, p-IIIa, p-IIIb and p-IIIc) that showed significant differences in PPS and OS. These findings demonstrate the heterogeneity of disease progression and prognosis after immunotherapy failure. Further validation in large cohorts is necessary to develop prognostic models that integrate distinct progression patterns to guide subsequent treatment decisions. Additionally, post-immunotherapy progression in patients with AFP levels ≥400ng/mL indicates a shortened median PPS. These findings provide valuable insights for future personalized treatment decisions.